Non-communicable disease risk factors and treatment preference of obese patients in Cape Town - Kathryn Manning; Marjanne Senekal; Janetta Harbron (AOSIS, 2016)
Background: Insights into the characteristics of treatment seekers for lifestyle changes and treatment preferences are necessary for intervention planning. Aim: To compile a profile of treatment-seeking obese patients with non-communicable diseases (NCDs) or NCD risk factors and to compare patients who choose group-based (facility-based therapeutic group [FBTG]) versus usual care (individual consultations) treatment. Setting: A primary healthcare facility in Cape Town, South Africa. Methods: One hundred and ninety-three patients were recruited in this cross-sectional study. Ninety six chose FBTG while 97 chose usual care. A questionnaire, the hospital database and patients' folders were used to collect data. Weight, height and waist circumference were measured. STATA 11.0 was used for descriptive statistics and to compare the two groups. Results: The subjects' mean age was 50.4 years, 78% were women and of low education levels and income, and 41.5% had type 2 diabetes, 83.4% hypertension and 69.5% high cholesterol. Mean (s.d.) HbA1c was 9.1 (2.0)%, systolic BP 145.6 (21.0) mmHg, diastolic BP 84.5 (12.0) mmHg, cholesterol 5.4 (1.2) mmol/L), body mass indicator (BMI) 39.3 (7.3) kg/m2 and waist circumference 117 (12.6) cm). These figures were undesirable although pharmacological treatment for diabetes and hypertension was in place. Only 14% were physically active, while TV viewing was > 2h/day. Mean daily intake of fruit and vegetables (2.2 portions/day) was low while added sugar (5 teaspoons) and sugar-sweetened beverages (1.3 glasses) were high. Usual care patients had a higher smoking prevalence, HbA1c, number of NCD risk factors and refined carbohydrate intake, and a lower fruit and vegetable intake. Conclusion: Treatment seekers were typically middle-aged, low income women with various modifiable and intermediate risk factors for NCDs. Patients choosing usual care could have more NCD risks. Keywords: Non-communicable diseases; primary health care; family medicine; obesity; diabetes; treatment preference; dietary intake; NCD risk factors; group-based treatment; stages of change